Calcium signaling in human stem cell-derived cardiomyocytes: Evidence from normal subjects and CPVT afflicted patients - Zhang, Xiao-Hua (Cell Calcium, 2015)
Derivation of cardiomyocyte cell lines from human fibroblasts (induced pluripotent stem cells, iPSCs) has made it possible not only to investigate the electrophysiological and Ca(2+) signaling properties of these cells, but also to determine the altered electrophysiological and Ca(2+)-signaling profiles of such cells lines derived from patients expressing mutation-inducing pathologies. This approach has the potential of generating in vitro human models of cardiovascular diseases where cellular pathology can be investigated in detail and possibly specific pharmacotherapy developed. Although this approach has been applied to a number of mutations in channel proteins that cause arrhythmias, there are only few detailed reports addressing Ca(2+) signaling pathologies beyond measurements of Ca(2+) transients in intact non-voltage clamped cells. Unfortunately full understanding of Ca(2+) signaling pathologies remains elusive, not only because of the plethora of Ca(2+) signaling proteins defects that cause arrhythmias and cardiomyopathies, but also because detailed functional properties of Ca(2+) signaling proteins are difficult to obtain. Catecholaminergic polymorphic ventricular tachycardia (CPVT1) is a malignant inherited arrhythmogenic disorder predominantly caused by mutations in the cardiac ryanodine receptor (RyR2). Thus far over 150 mutations in RyR2 have been identified that appear to cause this arrhythmia, a number of which have been expressed and studied in transgenic mice or cell-line models. The development of human iPSC-technology makes it possible to create human heart cell-lines carrying these mutations, making detailed identification of Ca(2+) signaling defects and its specific pharmacotherapy possible. In this review we shall first briefly summarize the essential characteristics of the mammalian cardiac Ca(2+) signaling, then compare them to Ca(2+) signaling phenotypes of human induced pluripotent stem cell derived cardiomyocytes (hiPSC-CM) and to those of rat neonatal cardiomyocytes, and categorize the possible variance in Ca(2+) signaling defects caused by different CPVT-inducing mutations as expressed in hiPSC-CMs.